MASA JABATAN JAKSA AGUNG DALAM PERSPEKTIF FIQH SIYASAH - Hanif Azhar (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2015)
The tenure of attorney general of Indonesia Republic that is not strictly regulated in the prosecutor law has created legal uncertainty. By descriptive analysis, this issue will be studied in fiqh siyasah (islamic political law). In the Indonesian state administration, the attorney general's tenure that is based on the constitutional convention, which was later confirmed by the Constitutional Court decision, is 5 years old. This assertion is intended to eliminate the legal uncertainty over the conditions governing the tenure. The regulations are in line with the general principles and rules of islamic law which are principle mashlah mursalah and tasharruf al-imam 'ala al-ra'iyyah manuthun bi al-maslahah.